Theories in Adult Learning and Education : A Book Review (International Journal of Multidisciplinary Perspectives in Higher Education, 2019)
Theories in adult learning and education is a book written in a form of study guide. The author divides the book into two parts. Part one describes the theories of learning; its definitions and its implications on adult learning and teaching. Part two focuses on the global trends of adults' participation in learning. The audience of the book are educators who involved in adult teaching and learning at secondary and post-secondary settings. Unlike traditional chapter books, this study guide challenges the reader by providing exercises and tasks. The purpose of the exercises and tasks is to invite the readers to reflect on their reading of the study guide and to facilitate the comprehension of the book. The book is a great reference in adult teaching and learning.